Investigation of selenium nutritional status and dietary pattern among children in Kashin-Beck disease endemic areas in Shaanxi Province, China using duplicate portion sampling method. (June 2022) - Ning, Yujie; Hu, Minhan; Chen, Sijie; Zhang, Feiyu; Yang, Xiaodong; Zhang, Qingping; Gong, Yi; Huang, Ruitian; Liu, Yanli; Chen, Feihong; Pei, Leilei; Guo, Xiong; et al.
Graphical abstract: Abstract: Background and objectives: Selenium deficiency is a primary risk factor of Kashin-Beck disease (KBD). This study aimed to investigate whether children in endemic areas could maintain sufficient selenium intake after termination of selenium supplement administration, and evaluate their comprehensive nutritional status and dietary structure. Methods: Duplicate portion sampling combined with a questionnaire was adopted to collect data on categories and quantity of all food ingested in three consecutive days. Occipital hair was also collected to detect selenium content by hydride generation atomic fluorescence spectrometry (HGAFS). CDGSS3.0 software and factor analysis were integrated to assess the children's comprehensive nutritional status and dietary structure. Results: This study included 240 sex-matched (1:1) children aged 7–12 years from KBD endemic (n = 120) and non-endemic (n = 120) areas. Overall, 720 solid food, 720 liquid, and 240 hair samples were collected for selenium determination. The mean selenium level in hair of children in endemic areas (0.38 ± 0.16 mg/kg) was significantly lower than that in children in non-endemic areas (0.56 ± 0.28 mg/kg, Z = −5.249, p  < 0.001). The dietary selenium intake of children in endemic areas was 40.0% lower than that in children in non-endemic areas (Z = −9.374, p <  0.001). Children in endemic areas consumed significantly less diverse dietary items leading to significantly less intake of multiple nutrients compared to children in non-endemic areas. Conclusions: The dietary selenium intake of most children in endemic areas was less than the recommended amount. The dietary structure of children was undiversified, which limited the intake of multiple nutrients. Therefore, comprehensive nutrition rather than sole selenium intake should be the primary concern in the future.